Hypoxia enhances ILC3 responses through HIF-1α-dependent mechanism - Fachi, J. L. (Mucosal Immunol, 2021)
Group 3 innate lymphoid cells (ILC3) have a prominent role in the maintenance of intestine mucosa homeostasis. The hypoxia-inducible factor (HIF) is an important modulator of immune cell activation and a key mechanism for cellular adaptation to oxygen deprivation. However, its role on ILC3 is not well known. In this study, we investigated how a hypoxic environment modulates ILC3 response and the subsequent participation of HIF-1 signaling in this process. We found increased proliferation and activation of intestinal ILC3 at low oxygen levels, a response that was phenocopied when HIF-1α was chemically stabilized and was reversed when HIF-1 was blocked. The increased activation of ILC3 relied on a HIF-1α-dependent transcriptional program, but not on mTOR-signaling or a switch to glycolysis. HIF-1α deficiency in RORyt compartment resulted in impaired IL-17 and IL-22 production by ILC3 in vivo, which reflected in a lower expression of their target genes in the intestinal epithelium and an increased susceptibility to Clostridiodes difficile infection. Taken together, our results show that HIF-1α activation in intestinal ILC3 is relevant for their functions in steady state and infectious conditions.